Isolation of Antibiotic Resistant Bacteria from Healthy Students and Staff of INTI International University - Chuah, Eric Han Lim (2016)
Disease related to antibiotic resistance in Malaysia is at a critical level because of the frequent misuse of antibiotics and this caused the emergence of antibiotic-resistant bacteria. It is important to isolate the antibiotic resistant bacteria and create more awareness towards antibiotic resistant bacteria among public. Methicillin resistant Staphylococcus aureus (MRSA) is one of the more serious antibiotic-resistant bacteria. Thus, the objectives of this project were to isolate antibiotic resistance bacteria from the nasal cavity and axilla of healthy individuals. Samples collected were cultures. As all isolates were Gram positive, they were grown on Mannitol Salt Agar (MSA) and subjected to catalase test. Antibiotic susceptibility testing was conducted to determine the susceptibility of bacteria towards antibiotics by using the disc diffusion method. Bacteria that were Gram-positive, cocci with cluster-like cell arrangement, was catalase positive, and resistant to oxacillin, were further subjected to inoculation on Brilliance MRSA 2 agar. This is because these bacteria indicate the likely presence of MRSA. In this study, 24 isolates were MRSA while 12 isolates are likely to be MRSE. However, the strains of the MRSA and MRSE could not be determined conclusively. Further tests such as DNA sequencing are required to confirm the identity of bacteria. This finding is important so that the staff and students of INTI International University can be alerted to prevent any possible outbreak of MRSA or MRSE-related diseases.